A hybrid ion-exchange fabric/ceramic membrane system to remove As(V), Zn(II), and turbidity from wastewater - Choi, Nag Choul; Cho, Kang Hee; Kim, Min Sung; Park, Seong Jik; Lee, Chang Gu (Applied Sciences (Switzerland), 2020)
Ceramic membranes and ion exchangers are effective at removing turbidity and ionic contaminants from water, respectively. In this study, we demonstrate the performance of a hybrid ion-exchange fabric/ceramic membrane system to treat metal ions and turbidity at the same time in synthetic wastewater. The removal rate of As(V) and Zn(II) by the ceramic membrane increased with solution pH, while turbidity was completely removed regardless of the solution pH. The main reaction of As(V) removal was adsorption at solution pH 6 and precipitation at solution pH 8, whereas phase-change was the predominant reaction for Zn(II) removal at both solutionpHvalues. The removal efficiency of the ion-exchange fabric was affected by the solution pH, with the maximum removal capacity of As(V) occurring at solution pH 4. The As(V) adsorption capacity of the ion-exchange fabric reached equilibrium within 120 min. The ion-exchange capacity of the ion-exchange fabric was compared with commercial ion-exchange fibers. The regeneration efficiency of the ion-exchange fabric using 0.1 M NaCl solution was around 95% on average and decreased slightly as the number of regeneration cycles was increased. Over 80% of As(V) and Zn(II) were steadily removed at solution pH 6 by the hybrid ion-exchange fabric/ceramic membrane system. Reduced flow rate and removal capacity were recovered through a backwashing process during continuous treatment with the hybrid ion-exchange fabric/ceramic membrane system.
Keywords: As(V) removal; Ceramic membrane; Ion-exchange fabric; Turbidity removal; Zn(II) removal